ICU bed # 7 - Arevalo, Rica (VideoFlick Productions], 2007)
ICU bed # 7 is a quiet, funny and moving family drama about an ailing father (Eddie Garcia) and how his two daughters (Angel Aquino and Irma Adlawan) are torn whether to end or prolong his life is one of the conflicts and highlights of ICU bed # 7